2007
DOI: 10.3310/hta11510
|View full text |Cite
|
Sign up to set email alerts
|

Systematic reviews of the clinical effectiveness and cost-effectiveness of proton pump inhibitors in acute upper gastrointestinal bleeding

Abstract: PPI treatment compared with placebo or H2RA reduces mortality following PU bleeding among patients with high-risk endoscopic findings, and reduces re-bleeding rates and surgical intervention. PPI treatment initiated prior to endoscopy in UGI bleeding significantly reduces the proportion of patients with SRH at index endoscopy but does not reduce mortality, re-bleeding or the need for surgery. The strategy of giving oral PPI before and after endoscopy, with EHT for those with major SRH, is likely to be the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
0
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(110 citation statements)
references
References 148 publications
(469 reference statements)
3
99
0
8
Order By: Relevance
“…Indeed, the eradication of H. pylori in highrisk patients prior to the initiation of NSAID therapy has been shown to significantly reduce the risk of subsequent ulceration (Bazzoli et al, 2001;Malfertheiner et al, 2002). Two systematic reviews have clearly shown that eradication of H. pylori is superior to placebo therapy in the primary prevention of peptic ulcers among NSAID users (risk ratio (95 % CI) 0.35 (0.20 -0.61)) (Leontiadis et al, 2007). Using a Markov model, Leontiadis et al (Leontiadis et al, 2007) showed that the most cost-effective strategy for primary prevention of NSAID-associated ulcers was H. pylori eradication in patients over age 50.…”
Section: Role Of Helicobacter Pylori Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, the eradication of H. pylori in highrisk patients prior to the initiation of NSAID therapy has been shown to significantly reduce the risk of subsequent ulceration (Bazzoli et al, 2001;Malfertheiner et al, 2002). Two systematic reviews have clearly shown that eradication of H. pylori is superior to placebo therapy in the primary prevention of peptic ulcers among NSAID users (risk ratio (95 % CI) 0.35 (0.20 -0.61)) (Leontiadis et al, 2007). Using a Markov model, Leontiadis et al (Leontiadis et al, 2007) showed that the most cost-effective strategy for primary prevention of NSAID-associated ulcers was H. pylori eradication in patients over age 50.…”
Section: Role Of Helicobacter Pylori Infectionmentioning
confidence: 99%
“…Systematic reviews have shown that double-dose (e.g., famotidine 40 mg two times daily) but not single-dose H2 receptor antagonists are effective at reducing the risk of NSAID-induced endoscopic gastric ulcers (Leontiadis et al, 2007;Rostom et al, 2002). In patients taking low-dose aspirin, famotidine 20 mg twice daily can reduce the development of oesophagitis, gastric and duodenal ulcers by 80% in an average-risk population, when compared with placebo therapy (Taha et al, 2009).…”
Section: H2 Receptor Antagonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most known treatment in management of UGIB since their introduction is the proton pump inhibitor is the most effective as its reduces mortality following peptic ulcer bleeding and also in preventing low dose aspirin use associated to upper gastrointestinal ulcers and bleedings but also as preventing GI disease in relation with NSAIDS use, which are a common auto medicated drug in our population being most common in elderly from the total, 114 patients were treated with proton pump inhibitor as literature says and 86.96% had an effective discharge [12][13][14].…”
Section: The Impact Of An Early Endoscopy In Ugibmentioning
confidence: 99%
“…Histamine H 2 -receptor antagonists (H2RAs) and proton pump inhibitors (PPIs) prevent this (Leontiadis et al 2007). However, chronic suppression of acid secretion by H2RAs or PPIs causes hypergastrinaemia.…”
Section: Introductionmentioning
confidence: 99%